Myotonic dystrophy health index: Correlations with clinical tests and patient function. Issue 2 (29th December 2015) - Heatwole, Chad; Bode, Rita; Johnson, Nicholas E.; Dekdebrun, Jeanne; Dilek, Nuran; Eichinger, Katy; Hilbert, James E.; Logigian, Eric; Luebbe, Elizabeth; Martens, William; Mcdermott, Michael P.; Pandya, Shree; et al.
ABSTRACT: Introduction : The Myotonic Dystrophy Health Index (MDHI) is a disease‐specific patient‐reported outcome measure. Here, we examine the associations between the MDHI and other measures of disease burden in a cohort of individuals with myotonic dystrophy type‐1 (DM1). Methods : We conducted a cross‐sectional study of 70 patients with DM1. We examined the associations between MDHI total and subscale scores and scores from other clinical tests. Participants completed assessments of strength, myotonia, motor and respiratory function, ambulation, and body composition. Participants also provided blood samples, underwent physician evaluations, and completed other patient‐reported outcome measures. Results : MDHI total and subscale scores were strongly associated with muscle strength, myotonia, motor function, and other clinical measures. Conclusions : Patient‐reported health status, as measured by the MDHI, is associated with alternative measures of clinical health. These results support the use of the MDHI as a valid tool to measure disease burden in DM1 patients. Muscle Nerve, 2015 Muscle Nerve 53: 183–190, 2016